Realizacja warunków dotyczących nupturientów w przypadku zawierania małżeństwa mieszanego przez katolika z wiernym Kościoła lub Wspólnoty kościelnej nie mającej pełnej łączności z Kościołem katolickim (kan. 1125, n. 1-3 KPK) - Dzierżon, Ginter (Ius Matrimoniale, 2016)
The author of the presented article focused his attention on the question of the realization of conditions concerning nupturients in the case of contracting a mixed marriage between a Catholic and a member of a Church or Ecclesial Community not in full communion with the Catholic Church. The analysis of can. 1125, n. 1-3 CIC shows that the conditions to be fulfilled before granting a permission concern mostly the Catholic and do not in any way infringe the religious liberty of the other party. According to the will of the legislator, the non-Catholic party is only obliged to meet the requirement codified in can. 1125, n. 3 CIC which remains in a close relation with the natural structure of marriage. This obligation is especially important since not sharing the Catholic concept of marriage as for the components crucial for the canonical system results in invalidity of marriage.